PbTe quantum dots highly packed monolayer fabrication by a spin coating method. - Svetlana Lyssenko; Michal Amar; Alina Sermiagin; Refael Minnes (PLoS ONE)
This study investigates the fabrication of large-area, highly-ordered monolayers of PbTe quantum dots (QDs) on TiO2/ITO substrate, using a fast, simple, and repeatable spin-coating technique. For the first time, a real monolayer (a layer with the height of a single QD) covering approximately 3 cm2 was successfully prepared, achieving a root-mean-square roughness (Rq) of 1.37 nm. The research systematically explores key parameters such as QD morphology, concentration, spin-coating conditions, substrate characteristics, wetting properties, and solvent effects to optimize thin film deposition. The findings reveal that the spin-coating method favors the formation of layers with spherical QDs (6-9 nm) over cubical QDs (10-13 nm). The findings highlight the significant influence of solvent evaporation rate, viscosity, and wettability on monolayer quality. Chloroform was identified as the optimal solvent for cubical QDs (~90% coverage), while hexane was more effective for spherical QDs (90%-100% coverage). Beyond monolayers, high-quality bilayers were also fabricated, demonstrating the method's potential for multilayer fabrication. This rapid and efficient method for monolayer and bilayer fabrication marks a significant breakthrough in producing uniform, large-area films, facilitating seamless integration with existing technologies. It offers a scalable and cost-effective solution, opening the door to broader applications in fields that demand high-quality thin film deposition.